Desiccation tolerance of cambuci seeds - Santoro, Marcelo Brossi; Brogio, Bruna do Amaral; Forti, Victor Augusto; Novembre, Ana Dionísia da Luz Coelho; Silva, Simone Rodrigues da (Comunicata Scientiae, 2020)
This work aimed to evaluate the interference of seed desiccation on the occurrence of root protrusion and the formation of normal cambuci seedlings. Seeds were obtained from mature fruits collected from adult plants and submitted to oven drying with forced air circulation at 30±2°C in order to obtain different water contents. The seeds were then submitted to the germination test in a completely randomized design at 25°C and 12 hours photoperiod, and were weekly evaluated for a period of 90 days, regarding the number of seeds with root protrusion, the number of dead seeds and normal seedlings. At the end the germination speed index (GSI) the mean germination time (MGT) and the average speed of germination (ASG) were calculated. Any of these variables were significantly affected until the water content decreased to 14.9%, whereas at 9.1% and 6.6% water contents, there was a significant reduction of root protrusion and GSI, and a higher percentage of dead seeds. Cambuci seeds tolerate desiccation down to 15% water content without losing viability.